PSYCHOLOGY OF CRIMINAL PERSONALITY - Ikramov Nizomiddin Nuriddinovich (American Journals, 2023)
The role of psychological knowledge is very important for the study of human activity in the field of law enforcement agencies. In-depth study of a person, his personality, basic psychological conditions, processes, is important in legal activity. To study the personality of a criminal, it is necessary to fight crime first. Psychology studies the mechanism of personal immunity in criminal situations and sets the main goal of crime prevention. Crime is a changing phenomenon that exists in human society. The fact that the state, level, and structure of criminality changes qualitatively and quantitatively during human development depends on the economic, social, and political legal changes in the society. In terms of quality, it is expressed in the method of execution, execution as an organized group, execution using modern science and technology achievements, etc.
Keywords: Criminal psychology, psychology, crime, criminal community, crime, law, protection, crime, detective, investigation.